The Formation of the Extrinsic Prothrombin Activator - Straub, W; Duckert, F (Thrombosis and Haemostasis, 1961)
The formation of the extrinsic activator of prothrombin conversion is investigated. We use the term “extrinsic activator” to avoid ambiguity which could arise when employing the name tissue thromboplastin.The experiments are carried out with purified clotting factors and congenital factor VII and X-deficient sera. Two steps can be distinguished. First, tissue factor and factor X react together as substrates in presence of Ca ions to form the extrinsic reaction product. The reaction is catalyzed enzymatically by factor VII. In the second stage, the reaction product and factor V (substrate) form the extrinsic activator which in turn can convert the prothrombin to thrombin.